ChemInform Abstract: Recent Progress in Direct Introduction of Fluorinated Groups on Alkenes and Alkynes by Means of C—H Bond Functionalization. Issue 12 (March 2015) - Besset, Tatiana; Poisson, Thomas; Pannecoucke, Xavier
Abstract Review: [direct functionalization of alkenes and alkynes with fluorine or fluorinated building blocks using photocatalyzed transformations, base‐promoted processes, and transition metal‐catalyzed reactions; 58 ref.